Consumer Protection Due to Music Festival Cancellation: Perlindungan Konsumen Akibat Dibatalkannya Festival Musik - Anshari , Muhammad Taher; Suprapti, Duhita Driyah (Annual Review of Legal Studies, 2024)
Consumer rights violations persist at music festivals due to errors and negligence by business actors, resulting in a disregard for legal protections and certainty. This failure in fulfilling legal responsibilities often leads to event cancellations. This study investigates two key issues: (1) Consumer protection following the cancellation of the 2022 Berdendang Bergoyang Festival, and (2) Dispute resolution efforts stemming from business actors' mistakes in the cancellation. Employing empirical juridical methods, including interviews, questionnaires, and document analysis, the research reveals loopholes allowing event organizers to bypass regulations, such as inadequate permits, facilitating exploitation by negligent parties. Resolution strategies involve non-litigation methods, such as mediation, aiming to refund tickets and compensate audiences. Litigation remains an option if agreements cannot be reached. The research concludes that consumer protection mechanisms often fail due to consumer vulnerability and business actors' lack of good faith. Recommendations include regulatory adjustments to eliminate loopholes, ensuring legal compliance and consumer welfare. Effective consumer dispute resolution requires both litigation and non-litigation approaches, emphasizing the importance of governmental and law enforcement intervention to safeguard consumer rights and promote legal certainty in festival arrangements.